Pathophysiological Role of Omega Pore Current in Channelopathies - Jurkat-Rott, Karin; Groome, James R.; Lehmann-Horn, Frank (Frontiers in Pharmacology, 2012)
In voltage-gated cation channels, a recurrent pattern for mutations is the neutralization of positively charged residues in the voltage-sensing S4 transmembrane segments. These mutations cause dominant ion channelopathies affecting many tissues such as brain, heart, and skeletal muscle. Recent studies suggest that the pathogenesis of associated phenotypes is not limited to alterations in the gating of the ion-conducting alpha pore. Instead, aberrant so-called omega currents facilitated by the movement of the S4 segments during activation and during recovery are thought to cause symptoms. Surprisingly, these omega currents display uni- or bi-directionality and conduct cations with varying ion selectivity. Additionally, the voltage-sensitivity enables the channels to conduct different omega currents in the various voltage ranges. This review gives an overview of voltage sensor channelopathies in general and focuses on pathogenesis of skeletal muscle S4 disorders for which current knowledge is most advanced.